KUFRI GARIMA-A NEW HIGH YIELDING TABLE POTATO VARIETY - Pande, PC; Luthra, S K; Singh, B P; Gupta, V K; Rawal, Sanjay (Potato Journal, 2015)
Kufri Garima is a medium maturing, main season, high yielding table purpose potato variety suitable for cultivation in Indo-gangetic plains and plateau regions. It is a clonal selection from a cross between PH/F-1045 and MS/82-638. Its plants are medium tall and vigorous with field resistance to late blight. It produces light yellow, ovoid tubers with shallow eyes and light yellow flesh. It possesses good keeping quality and has moderate tuber dry matter (18%). It is capable of yielding 35-40 t/ha under optimum agronomical practices.